Combination Therapy of Ursodeoxycholic Acid and Corticosteroids for Primary Biliary Cirrhosis with Features of Autoimmune Hepatitis: A Meta-Analysis - Yan Zhang; Jie Lu; Weiqi Dai; Fan Wang; Miao Shen; Jing Yang; Rong Zhu; Huawei Zhang; Kan Chen; Ping Cheng; Lei He; Chengfen Wang; et al. (Gastroenterology Research and Practice)
A meta-analysis was performed of RCTs comparing therapies that combine UDCA and corticosteroids with UDCA monotherapy. In this paper, we found that the combination therapy of UDCA and corticosteroids was more effective for PBC-AIH.